Adrenocortical insufficiency after bilateral adrenal hemorrhage due to anticoagulation and chronic immunothrombocytopenia - Sophie Charlotte Hintze; Felix Beuschlein (Endocrinology, Diabetes & Metabolism Case Reports)
Adrenocortical insufficiency is defined as the clinical manifestation of chronic glucocorticoid and/or mineralocorticoid deficiency due to failure of the adrenal cortex. It may result in an adrenal crisis, which is a life-threatening disease; thus, prompt initiation of therapy with hydrocortisone is necessary. Symptoms such as hypotension, weight loss, or fatigue are not specific, which is why diagnosis is delayed in many cases. Our patient suffered from immune thrombocytopenia (ITP), an acquired thrombocytopenia caused by an autoimmune reaction against platelets and megakaryocytes. Primary ITP, in which no triggering cause can be identified, must be distinguished from secondary forms (e.g. in the context of systemic autoimmune diseases, lymphomas, or (rarely) by drugs). Patients may be asymptomatic at presentation or may present with a range of mild mucocutaneous to life-threatening bleeding. Here, we report on a 43-year-old woman who had developed adrenocortical insufficiency due to bilateral hemorrhage in the adrenal glands. Because of anticoagulation with phenprocoumon after pulmonary embolism and thrombocytopenia on the basis of ITP, the patient had an increased risk of bleeding. Due to the nonspecific and ambiguous symptoms of adrenocortical insufficiency, prompt diagnosis remains a challenge.